Pneumococcal conjugate vaccine use for the prevention of pneumococcal disease in adults <50 years of age. (2nd January 2018) - Isturiz, Raul E.; Hall-Murray, Cassandra; McLaughlin, John M.; Snow, Vincenza; Schmoele-Thoma, Beate; Webber, Chris; Thompson, Allison; Scott, Daniel A
ABSTRACT: Introduction ; Adults, particularly those with underlying chronic conditions, eg, cardiovascular, liver, and pulmonary diseases and diabetes mellitus, have a persistent pneumococcal disease burden. Thirteen-valent pneumococcal conjugate vaccine (PCV13) is recommended in the United States for all adults aged ≥65 years and immunocompromised adults aged <65 years to protect against vaccine-serotype (VT) invasive pneumococcal disease (IPD) and pneumonia. PCV13 is not recommended for immunocompetent adults aged ≥18 years with comorbidities associated with increased pneumococcal disease risk. Areas covered : This US-focused review summarizes PCV13-type IPD and community-acquired pneumonia burden in adults aged <50 years, PCV13 immunogenicity and safety in this population, and adult pneumococcal vaccination recommendations. Expert commentary : Considering (i) PCV13 has demonstrated efficacy against VT-IPD and pneumonia in adults aged ≥65 years (with or without underlying chronic conditions), and (ii) immune responses to PCV13 in younger adults are comparable or better than in older adults, PCV13 would likely have similar efficacy in adults aged <50 years. Recommending PCV13 for at-risk adults aged <50 years would provide direct immunologic benefit of a conjugate vaccine and could address an important unmet medical need for pneumococcal pneumonia prevention. Although not directly addressed here, this benefit would likely extend to at-risk adults aged 50–64 years.